An evaluation of Scottish green health prescriptions using the APEASE criteria - Howlett, Neil; Freethy, Imogen; Harding, Sian; Wagner, Adam P.; Miners, Lisa; Anne-Greco, Honey; Lamming, Laura; Lloyd, Nigel; Brown, Katherine E. (BMC family practice, 2025)
Background Time spent in green space such as parks and forests can have positive effects on physical and mental health. Green Health Partnerships were set up in Scotland to promote use of green space for health improvement. One of the main mechanisms to achieve this was the setup of Green Health Prescriptions (GHPr). This study evaluates three GHPrs in different localities across a range of feasibility elements, and the funding and resourcing associated with implementation. Methods Interviews were conducted across service user, referrer, link worker, and activity provider groups across Dundee, Highland, and North Ayrshire. Interviews were deductively analysed using the APEASE (Acceptability, Practicability, Effectiveness, Affordability, Spillover effects, Equity) criteria. Data within each APEASE domain was then inductively coded producing more reflexive sub-themes. Data on funding and resources associated with delivering each programme was also collected to provide further context to the APEASE criteria. Results All stakeholder groups generally found the concept of using green spaces and the GHPr acceptable, and, although service users perceived that staff were often good communicators, there were times where awareness of and knowledge about the GHPr were lacking. There were reported improvements across a wide range of physical and mental health, and social outcomes for service users. The GHPr was also considered affordable in terms of the green health activity sessions. A key issue for staff across practicability, acceptability, and with monitoring equity, was the lack of underpinning IT infrastructure for referrals, communication with link workers, and data capture to reflect on service user progress. As implemented in Dundee, progression through the GHPr, after initial referral, took on average 195 min, at a cost of £64 per service user. Conclusions This evaluation highlighted the potential benefits for service users that can be realised through a GHPr. However, a lack of supportive systems to capture referral information, communicate between professionals, and document service user progress limits a more robust and extensive evaluation of the current GHPr model. Evaluation registration Research Registry identifier: researchregistry9069, registration date: 25/04/23.